A study on the usability and usefulness of Filipiniana.net digital library - Tingson, Leanne Pearl Dreo (School of Library and Information Studies, University of the Philippines Diliman, 2011)
The development of digital libraries is steadily increasing and it is the concern of the Library and Information Science community to ensure that the users get quality information from this new advent. In order to do so evaluation of libraries as determined by patrons and end-users must be performed.